The role of accounting in the age of Artificial Intelligence: systematic review from 2020 to 2025 - Costa-Climent, Ricardo; Haftor, Darek (JOINETECH, 2025)
Over the last decade, the accounting function has evolved from a role focused on recording and compliance to that of a strategic partner to management. This systematic review of the literature from 2020 to 2025 explores how artificial intelligence (AI) is disrupting accounting by automating processes, generating predictive information and supporting decision-making. Five objectives are examined: (1) mapping the evolution of accounting within the company; (2) classifying AI applications according to technologies and processes; (3) assessing the impact of AI on the quality and use of accounting information; (4) analysing the relationship between accounting AI and value creation; and (5) identifying contingent factors and barriers. The results indicate that adopting AI enables accounting to free up time from routine tasks and to collaborate actively in the design of the business model. The technologies used range from machine learning and language processing to intelligent robotics, applied to automation, forecasting, and anomaly detection. AI improves the accuracy and timeliness of information, though it poses challenges in terms of explainability and governance. Value creation depends on the right combination of data, analytical capabilities and good governance. The review reveals barriers such as data quality, implementation costs and cultural resistance, and proposes a configurational framework linking AI, processes, information, management decisions and value creation.